2011
DOI: 10.2176/nmc.51.337
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Ebselen Following Forebrain Ischemia: Involvement of Glutamate and Nitric Oxide

Abstract: Ebselen is a mimic of glutathione peroxidase that reacts with peroxynitrite and inhibits nitric oxide (NO) synthase. Ebselen has beneficial effects on the neurological outcome of patients with stroke. In this study, the mechanisms by which ebselen can elicit neuroprotective effects against ischemic brain injury were investigated in male Wistar rats. Experimental forebrain ischemia was induced by bilateral common carotid artery occlusion with hemorrhagic hypotension. Ebselen was administered to animals in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
(55 reference statements)
3
17
0
1
Order By: Relevance
“…The similar effect on mitochondrial level and function was observed in SelH overexpressing HT22 cells [88]. Moreover, the SelH elevated the mitochondrial biogenesis through activation of protein kinase A-CREB-PGC-1α and Akt/protein kinase B-CREB-PGC-1α pathways [89].…”
Section: Selenium and Selenoproteins In Neuro-logical Disorderssupporting
confidence: 67%
“…The similar effect on mitochondrial level and function was observed in SelH overexpressing HT22 cells [88]. Moreover, the SelH elevated the mitochondrial biogenesis through activation of protein kinase A-CREB-PGC-1α and Akt/protein kinase B-CREB-PGC-1α pathways [89].…”
Section: Selenium and Selenoproteins In Neuro-logical Disorderssupporting
confidence: 67%
“…Ebselen has been extensively used in a variety of experimental animal models of injury/disease [37] and as a neuroprotectant in the treatment of patients following acute ischemic stroke [4042] and aneurysmal subarachnoid hemorrhage [43]. A clinical trial is currently underway to determine the utility of ebselen in a hearing loss paradigm [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, in these models, NOX2ds-tat was applied via a cranial window, which almost excludes these studies as valuable proof of concepts for NOX inhibition in human therapy of these diseases. Several studies suggested a protection by deleting NOX2 in brain ischemia reperfusion injury, some by applying unspecific inhibitors such as apocynin, DPI (120), or ebselen (90) [reviewed in ref. (140)].…”
Section: Fig 7 Nox Enzymes As Validated Therapeutic Targetsmentioning
confidence: 99%